Conserved mechanisms of tumorigenesis in the Drosophila adult midgut. - Òscar Martorell; Anna Merlos-Suárez; Kyra Campbell; Francisco M Barriga; Christo P Christov; Irene Miguel-Aliaga; Eduard Batlle; Jordi Casanova; Andreu Casali (PLoS ONE)
Whereas the series of genetic events leading to colorectal cancer (CRC) have been well established, the precise functions that these alterations play in tumor progression and how they disrupt intestinal homeostasis remain poorly characterized. Activation of the Wnt/Wg signaling pathway by a mutation in the gene APC is the most common trigger for CRC, inducing benign lesions that progress to carcinomas due to the accumulation of other genetic alterations. Among those, Ras mutations drive tumour progression in CRC, as well as in most epithelial cancers. As mammalian and Drosophila's intestines share many similarities, we decided to explore the alterations induced in the Drosophila midgut by the combined activation of the Wnt signaling pathway with gain of function of Ras signaling in the intestinal stem cells. Here we show that compound Apc-Ras clones, but not clones bearing the individual mutations, expand as aggressive intestinal tumor-like outgrowths. These lesions reproduce many of the human CRC hallmarks such as increased proliferation, blockade of cell differentiation and cell polarity and disrupted organ architecture. This process is followed by expression of tumoral markers present in human lesions. Finally, a metabolic behavioral assay shows that these flies suffer a progressive deterioration in intestinal homeostasis, providing a simple readout that could be used in screens for tumor modifiers or therapeutic compounds. Taken together, our results illustrate the conservation of the mechanisms of CRC tumorigenesis in Drosophila, providing an excellent model system to unravel the events that, upon mutation in Apc and Ras, lead to CRC initiation and progression.